Peruvian-Bolivian Trade in the Border Town of Desaguadero. An Approach to Economic and Social Dynamics from the Point of View of the Retailer - Puma-Llanqui, Javier Santos; Incacutipa-Limachi, Duverly Joao; Antezana-Bustinza, David Benjamín; Zevallos-Yana, Julio Fitzgerald; Tintaya-Choquehuanca, Olimpia (Journal of Ecohumanism, 2024)
The objective of the research is to analyze the commercial activity and the exchange of products on the border, analyzing the economic dynamics and the strategic role of commercial exchange in the cities of Desaguadero, a similar name for both border cities of Peru and Bolivia. The method used is qualitative, using in-depth interviews and direct observation as a research technique, which allowed us to analyze the strategies of exchange, commercial interactions and their impact on the economic life of local families in both countries. The results reveal how cross-border trade exchange contributes to the complementarity of the family economy in the region, boosting the economic dynamics of adjacent rural communities. However, the vast majority of products do not pass-through customs regulations, being classified as contraband. This trade is rooted in a tradition of commercial exchange that dates back to before the formation of Peru and Bolivia as independent countries. In conclusion, the complementarity observed in consumption and production patterns between Peru and Bolivia in this region underlines the importance of the cities of Desaguadero as a vital axis for the economic sustainability of rural communities along the border, strengthening family economies and promoting regional economic development.